(untitled) (Butwal Campus Journal, 2024)
This study uses a quantitative analysis based on a rapid questionnaire survey with 130 respondents from two wards that were purposefully chosen to investigate the dynamics of tourism in Devdaha Municipality, Nepal. The survey looked at a number of topics, such as the kinds of tourists that come to Devdaha, major stakeholders involving on it, how much people know about it as a pilgrimage site, how tourism affects local jobs and revenue. The results show that domestic travelers make up the majority of visitors, and a sizable percentage of respondents acknowledged the locations of Buddhist pilgrimages. Although governmental and non-governmental stakeholders are present, opinions about the professionalism and service qualities are critically observed. The paper also notes the expected advantages of tourism in fostering cross-cultural interchange and bolstering the local economy, while highlighting the major obstacles, such as infrastructure, promotional activities and economic concerns.